ATRP-based synthesis and characterization of light-responsive coatings for transdermal delivery systems - Anja C Pauly; Katrin Schöller; Lukas Baumann; René M Rossi; Kathrin Dustmann; Ulrich Ziener; Damien de Courten; Martin Wolf; Luciano F Boesel; Lukas J Scherer (Science and Technology of Advanced Materials, 2015)
The grafting of poly(hydroxyethylmethacrylate) on polymeric porous membranes via atom transfer radical polymerization (ATRP) and subsequent modification with a photo-responsive spiropyran derivative is described. This method leads to photo-responsive membranes with desirable properties such as light-controlled permeability changes, exceptional photo-stability and repeatability of the photo-responsive switching. Conventional track etched polyester membranes were first treated with plasma polymer coating introducing anchoring groups, which allowed the attachment of ATRP-initiator molecules on the membrane surface. Surface initiated ARGET–ATRP of hydroxyethylmethacrylate (where ARGET stands for activator regenerated by electron transfer) leads to a membrane covered with a polymer layer, whereas the controlled polymerization procedure allows good control over the thickness of the polymer layer in respect to the polymerization conditions. Therefore, the final permeability of the membranes could be tailored by choice of pore diameter of the initial membranes, applied monomer concentration or polymerization time. Moreover a remarkable switch in permeability (more than 1000%) upon irradiation with UV-light could be achieved. These properties enable possible applications in the field of transdermal drug delivery, filtration, or sensing.